Steering kinematics for a center-articulated mobile robot. - Corke, P.I (IEEE Transactions on robotics and automation)
This paper discusses the steering kinematics for a center-articulated mobile robot. Several models have been recently proposed in the literature and we use experimental data to compare and validate these models. The vehicle heading response to steering command is shown to include a dominant zero due a nonholonomic constraint, and this is verified by experiments conducted using a 30-t mobile vehicle at our laboratory. Simulation results are then used to show the significance of this zero and its effect on closed-loop heading angle control